Serum Ratio of Free Triiodothyronine to Thyroid-Stimulating Hormone: A Novel Index for Distinguishing Graves’ Disease From Autoimmune Thyroiditis - Wu, Zhiyong; Zhu, Yu; Zhang, Min; Wang, Chen; Zhou, Lingli; Liu, Wei; Yang, Wenjia; Li, Meng; Zhang, Simin; Ren, Qian; Han, Xueyao; Ji, Linong (Frontiers in Endocrinology, 2021)
Objective Graves’ disease (GD) and autoimmune thyroiditis (AIT) are two major causes of thyrotoxicosis. Correct diagnosis is a key step for their proper treatment. The objective of this study is to evaluate the usefulness of the thyroid-related parameters and identify new index for differential diagnosis of thyrotoxicosis Design A retrospective study based on the electronic medical records in Peking University People’s Hospital, Beijing, China. Methods 650 patients with GD and 155 patients with AIT from Dec, 2015 to OCT, 2019 were included in sample 1. 133 patients with GD and 14 patients with AIT from Dec, 2019 to Aug, 2020 were included in sample 2 for validating the novel index identified in sample 1. All the patients were Chinese and newly diagnosed. The thyroid-related clinical information before interventions was collected by reviewing the electronic medical records in hospital. Receiver operation curve (ROC) was used to obtain the optimal cutoff to differentiate GD from AIT. Results In sample 1, TSH receptor antibody (TRAb) is the best indicator to differentiate the GD from AIT, the area under ROC is 0.99（95%CI: 0.98-0.99,p<0.0001）,the optimal cutoff is 0.84IU/l with 98% sensitivity and 99% specificity. The AUC of free triiodothyronine (FT3)/thyroid stimulating hormone (TSH) ratio (FT3/TSH) is 0.86(95%CI: 0.84-0.88, p<0.0001), the optimal cutoff is 1.99pmol/mIU with 79% sensitivity and 80% specificity, its effectiveness was confirmed in sample 2(81% sensitivity and 100% specificity). Conclusions FT3/TSH ratio is a new useful index for differential diagnosis of thyrotoxicosis.